E-procurement success factors measurement in Indonesia: a trust-based formation model - Nanang, Herlino; Misman, Ahmad Fatzilah; Zulkifli, Zahidah (Institute of Electrical and Electronics Engineers, Inc., 2019)
Technological progress is now highly developed, especially in the government sector. E-Procurement is part of technology-based technology with the aim of supporting services in the field of services and procurement. In terms of implementation, there have been many advances and successes, this can be seen from the many studies relating to the progress of the system. With the implementation of the e-procurement system in Indonesia, it is expected to increase in services in the field of government services and competition between users runs well. This study investigates the measuring of whether there are relations in implementation of e-procurement in Indonesia with an element of trust and risk, an initiative that refers to the purchase of goods and services to the organization.